Occult level IV metastases in clinically node-negative patients with oral tongue squamous cell carcinoma. Issue 5 (20th April 2016) - Motiee-Langroudi, M; Amali, A; Saedi, B; Emami, H; Ensani, F; Lotfi, A; Rabbani Anari, M
Abstract: Objective: The present study was conducted to determine the rate of level IV lymph node involvement among node-negative (N0 ) necks in patients with squamous cell carcinoma of the tongue. Methods: The study comprised 32 patients with squamous cell carcinoma of the tongue, with tumour–node–metastasis staging of T1–3 N0 M0, who were admitted to the Otolaryngology Department at Tehran University of Medical Sciences from March 2012 to March 2014. After a complete diagnostic evaluation, wide primary tumour excision (with 1.5–2 cm margins) and extended supraomohyoid neck dissection (levels I–IV) were accomplished. Results: Occult metastasis was found in 28 per cent of the patients. Level I, II and III metastases were the most common (18.75, 18.75 and 15.62 per cent, respectively). Level IV metastasis was found in 6.25 per cent of patients. Conclusion: Supraomohyoid neck dissection appears to be an appropriate treatment for N0 tongue squamous cell carcinoma and there is no need for level IV lymph node dissection in a N0 patient.